Linking Up and Reaching Out in Bangladesh : Information and Communications Technology for Microfinance - Bagazonzya, Henry K; Safdar, Zaid; Abdullah, A.K.M; Niang, Cecile Thioro; Rahman, Aneeka (World Bank, 2012)
This book presents a new paradigm for introducing technology in the microfinance industry of Bangladesh that could help ameliorate current constraints. Under the new paradigm, a centralized Information and communication technology (ICT) platform will be established to serve the microfinance industry of Bangladesh and technology will be deployed more rapidly to Microfinance Institutions (MFIs) in all parts of the microfinance value chain, from the head office to branch offices, loan officers, and clients. Unlike in the traditional paradigm, the technology needs of all MFIs will be pooled together in one central office. The central office will offer technology tools, services, and know-how to MFIs throughout the country. Several benefits will be achieved under this new paradigm: i) because all technology needs will be pooled in one place, the central office will be able to exploit economies of scale and offer technology services to MFIs at a lower cost; and ii) because their technology needs will be outsourced, MFI staff will no longer need to devote as much time and effort to learning new technologies. The central office will provide all technology-related training and support.